Determinants of Economic Growth: Case of Indonesia - Raka Putra Paksi (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2020)
Economic growth has been an indicator to measure the capability of a nation to improve its citizen welfare. However, in recent years Indonesia’s economic growth has not been able to move up from 5 percent rate. This research intends to analyze factors that influence Indonesia’s economic growth in 1991-2019. By using OLS method, the result shows that export and household consumption growth has positive effect on economic growth. Labor growth does not have any impact, and inflation negatively affects economic growth